Project-Based Learning as an Alternative to the Pedagogy of Poverty in Low-Income Schools - Giesige, Shannon N. (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2018)
The pedagogy of poverty is a phrase coined by Martin Haberman in 1991 to describe the didactic teacher-centered learning that takes place in most urban, low-income schools. This form of teaching is based on assumptions that teachers, administrators, and parents make about the students they are teaching and the students’ goals, aims and capabilities. This manuscript discusses why teachers turn to the pedagogy of poverty and how project-based learning offers a workable alternative in a low-income, urban environment. It examines how project-based learning can improve student self-efficacy and academic performance, as well as exploring what this method asks of teachers.